2018
DOI: 10.3390/soilsystems2040059
|View full text |Cite
|
Sign up to set email alerts
|

Hot Spots and Hot Moments of Soil Moisture Explain Fluctuations in Iron and Carbon Cycling in a Humid Tropical Forest Soil

Abstract: Soils from humid forests undergo spatial and temporal variations in moisture and oxygen (O2) in response to rainfall, and induce changes in iron (Fe) and carbon (C) biogeochemistry. We hypothesized that high rainfall periods stimulate Fe and C cycling, with the greatest effects in areas of high soil moisture. To test this, we measured Fe and C cycling across three catenas at valley, slope, and ridge positions every two days for a two-month period in a rainforest in Puerto Rico. Over 12 days without rain, soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 77 publications
2
34
0
Order By: Relevance
“…where E a is the activation energy, A is the pre-exponential factor, R is the universal gas constant (8.314 J K −1 mol −1 ), and T is temperature in kelvin (K). Relationships between total C and biogeochemical parameters were analyzed using linear mixed-effects models with the lme4 package (Bates et al, 2015) in Rstudio. Regression analyses were conducted for the entire year-long dataset and for the growing and nongrowing seasons defined as May through September and October through March, respectively.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…where E a is the activation energy, A is the pre-exponential factor, R is the universal gas constant (8.314 J K −1 mol −1 ), and T is temperature in kelvin (K). Relationships between total C and biogeochemical parameters were analyzed using linear mixed-effects models with the lme4 package (Bates et al, 2015) in Rstudio. Regression analyses were conducted for the entire year-long dataset and for the growing and nongrowing seasons defined as May through September and October through March, respectively.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A recent study along hillslope transects in tropical forest soils representing an oxygen gradient (Hall and Silver, 2015), for example, found that a combination of Fe (II) (a proxy for reducing conditions), fine root biomass, and total Fe and Al concentrations explained the most variation of surface soil C content. How the relationships between C and important biogeochemical controls differ in systems that are subject to seasonal flooding is still in question, especially with depth (Barcellos et al, 2018).…”
mentioning
confidence: 99%
“…Tropical wet forest ecosystems are characterized by year‐round precipitation and pronounced seasonality, with drier periods still receiving more than 60 mm per month. Soil CO 2 concentrations in tropical soils can change markedly on weekly, monthly, and seasonal timescales, with substantially higher soil CO 2 levels in wet versus drier periods (Barcellos, O'Connell, Silver, Meile, & Thompson, 2018; Fernandez‐Bou et al, 2018; O'Connell, Ruan, & Silver, 2018; Schwendenmann & Veldkamp, 2006; Schwendenmann, Veldkamp, Brenes, O'Brien, & Mackensen, 2003). For wet rainforest soils in Costa Rica, Schwendenmann and Veldkamp (2006) reported that 75% of the CO 2 production occurred in the upper 0.5 m of the soil profile, attributing this to the lack of water stress and related shallow root biomass distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, after this initial increase, the damage in the canopy may lead to the opposite effect, and may open the soil to drying and to large diurnal variations in soil CO 2 respiration (Vargas & Allen, 2008a); this is a major driver of the nitrogen cycling and belowground carbon dynamics (Hasselquist, Santiago, & Allen, 2010). Regardless of mechanisms, short‐term fluctuations in soil CO 2 concentrations (and other greenhouse gases) lead to variability in soil emissions (Barcellos et al., 2018; Fernandez‐Bou, Dierick, & Harmon, 2020; Fernandez‐Bou et al, 2018; Harms & Grimm, 2008; Haverd, Ahlström, Smith, & Canadell, 2017; Kuzyakov & Blagodatskaya, 2015; Leon et al., 2014; Lubbers, Berg, Deyn, van der Putten, & van Groenigen, 2019; Soper et al., 2019; Swanson et al., 2019; Vargas et al., 2018). In this work, we monitor soil CO 2 concentration over multiple years to better understand its short‐term dynamics and potential influence on tropical soil CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The timescales of oxic and anoxic conditions, which are so crucial for the Fe redox dynamics previously discussed, are then intimately linked to the fluctuations in soil water content, which controls the diffusion of O 2 (Brady & Weil, 2016). Experimental evidence (Barcellos, O'Connell, et al, 2018;Hall et al, 2013) indeed suggests that, at the time scales of interest here, oxygen content is strongly related to the level of soil moisture, the former remaining high (≈20%) for water contents up to the so-called field capacity and then rapidly declining to ≈0% at saturation, when microbes and labile C exist to stimulate O 2 consumption (Keiluweit et al, 2018;Parkin, 1987;Silver et al, 1999). Soil moisture dynamics are linked to the soil, plant, and atmospheric conditions; the frequency and depth of rainfall events, evapotranspiration from soil and plants, and soil properties jointly determine the temporal evolution of soil oxic and anoxic conditions.…”
Section: Linking Oxic/anoxic Cycles To Rainfall Frequency and Intensimentioning
confidence: 99%